"I was still very young": agency, stigma and HIV care strategies at school, baseline results of a qualitative study among youth in rural Kenya and Uganda. (12th July 2022) - Johnson‐Peretz, Jason; Lebu, Sarah; Akatukwasa, Cecilia; Getahun, Monica; Ruel, Theodore; Lee, Joi; Ayieko, James; Mwangwa, Florence; Owino, Lawrence; Onyango, Anjeline; Maeri, Irene; Atwine, Frederick; et al.
Abstract: Introduction: Adolescents and young adults living with HIV (AYAH) have the lowest rates of retention in HIV care and antiretroviral therapy (ART) adherence, partly due to the demands of school associated with this life stage, to HIV‐related stigma and to fears of serostatus disclosure. We explore the implications of school‐based stigma and disclosure on the development of agency during a critical life stage in rural Kenya and Uganda. Methods: We conducted a qualitative study in the baseline year of the SEARCH Youth study, a combination intervention using a life‐stage approach among youth (15–24 years old) living with HIV in western Kenya and southwestern Uganda to improve viral load suppression and health outcomes. We conducted in‐depth, semi‐structured interviews in 2019 with three cohorts of purposively selected study participants (youth [ n = 83], balanced for sex, life stage and HIV care status; recommended family members of youth [ n = 33]; and providers [ n = 20]). Inductive analysis exploring contextual factors affecting HIV care engagement revealed the high salience of schooling environments. Results: Stigma within school settings, elicited by non‐consensual serostatus disclosure, medication schedules and clinic appointments, exerts a constraining factor around which AYAH must navigate to identify and pursue opportunities available to them as young people. HIV status can affect cross‐generational support and cohort formation, as AYAH differ from non‐AYAH peers because of care‐related demands affecting schooling, exams and graduation. However, adolescents demonstrate a capacity to overcome anticipated stigma and protect themselves by selectively disclosing HIV status to trusted peers and caregivers, as they develop a sense of agency concomitant with this life stage. Older adolescents showed greater ability to seek out supportive relationships than younger ones who relied on adult caregivers to facilitate this support. Conclusions: School is a potential site of HIV stigma and also a setting for learning how to resist such stigma. School‐going adolescents should be supported to identify helpful peers and selectively disclose serostatus as they master decision making about when and where to take medications, and who should know. Stigma is avoided by fewer visits to the clinic; providers should consider longer refills, discreet packaging and long‐acting, injectable ART for students.